Complex Evaluation of the Economic Security of the Regions of Ukraine (on the example of Ivano-Frankivsk oblast) (Economics and region, 2018)
Economic security in the regional dimension is a complex and multifaceted concept which in present-day conditions reflects the complex transient processes of economic development and transformation. All administrative entities without exception are interrelated and interdependent, and influenced by globalization and regionalization, integration of economic activity, economic and social policy. Only on condition of the synthetic use of theory and practice of security management it is possible to make an adequate assessment of a region, to give recommendations on its further development in the economic space. The aim is to develop theoretical, methodological and applied approaches to assessing the process of guaranteeing economic security in a regional dimension. In accordance with the stated purpose in the theoretical aspect, international and national experience of assessing the economic security of individual regions and the country as a whole has been analyzed. In the methodological plan, an assessment of the static and dynamic components of security has been proposed and tested. A system of assessing factors influencing the level of security of the region has been given: competitive, innovative, socio-economic development (depression) and globalization. In the applied aspect, calculations of the economic security level of Ivano-Frankivsk oblast for the period of 2013 – 2016 have been made. Variability of the factors of influence on the economic security level of Ivano-Frankivsk region has been analyzed and assessed. A temporal and factor security model has been developed, the results of which proved a significant dependence of the economic security on the influence of genetic factors and the real absence of the influence of such factor as time. The factorial model showed a positive impact of the indices of innovation capacity and globalization on the state of security and a negative influence of the other two factors. On the basis of the obtained data, two strategic goals and priority areas of the region’s development have been formulated and suggested. The practical value of the obtained results is the possibility of applying the developed theoretical and methodological approach to the development of proposals and recommendations aimed at prioritizing of socio-economic development of the region.
Keywords: economic security; econometric modeling; development strategy; static and dynamic security